Implementation of the Gianyar Aman Sejahtera Regional People's Business Credit Program (KURDA GAS) in Pre-Prosperous Community MSMEs - Kurniawan, I Gusti Ngurah; Widanti, Ni Putu Tirka; Widnyani, Ida Ayu Putu Sri (PT FORMOSA CENDEKIA GLOBAL, 2024)
KURDA GAS was launched to help the community in obtaining capital without the need for collateral, especially for the underprivileged. The purpose of this study is to find out how the Implementation of the Gianyar Aman Sejahtera Regional People's Business Credit Program (KURDA GAS) in MSMEs of the Underprivileged Community. This study uses a qualitative descriptive research method with an inductive approach. This research was conducted at PT. BPR Regional Bank Gianyar (Perseroda) The results of the study show several factors that cause the KURDA GAS program to not be maximized. Inhibiting Factors: Lack of Understanding and Knowledge, Complicated Administrative Procedures, Weak Business Capacity and Management, Limited Guarantees, Market Competition. Supporting Factors: Local Government Support, Training and Assistance Programs, Improved Economic Conditions, Partnerships with Financial Institutions, Infrastructure and Access to Technology.